Shining a Light on State Campaign Finance An Evaluation of the Impact of the National Institute on Money in State Politics - McGovern, Geoffrey (RAND Corporation, 2014)
The National Institute on Money in State Politics collects, processes, and makes public information on campaign contributions made to state-level candidates for public office. Drawing on experiences of a variety of users, as well as a review of the publications that have used the Institute's data and research reports, this report provides an evaluation of the Institute's impact on the public discourse over campaign finance at the state level.